Osun State partners IITA to boost Agriculture - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Osun State government, on Thursday June 1st 2017, in collaboration with the International Institute of Tropical Agriculture (IITA), Ibadan launched a research and farm training institute at Ago Owu area in Ayedaade local government area of the state as parts of the moves to transform agriculture sector. Launching the research and farm training institute, at Ago Owu Farm Settlement, Governor Rauf Aregbesola said the development would put a permanent end to myriad of challenges, confronting farmers in the state. He disclosed that the state had released 205.5 hectares of land for the take-off of the programme, just as he attributed the success of the scheme to unflinching support which the state received from the officials of the IITA to boost agricultural productions. Describing Governor the institute as a “citadel of knowledge in agriculture”, Aregbesola said with its establishment, all challenges confronting farming and farmers would be put behind, adding that the institution has the capacity to train, retrain and conduct various researches that would not only increase farmers’ yields but also expose them to modern agriculture practices. He said the scheme was part of his administration’s six-point integral action plan to increase on the agricultural produce, improve the welfare of farmers and turn Osun to food basket of the South West Nigeria. According to Aregbesola, “we must thank the IITA for the partnership we have because with the establishment of this training institute, our partnership is not just a memorandum on paper but rather a memorandum actualised. IITA has been an open partner with Osun government and the partnership was formalised in 2015 after a Memorandum of Understanding was mutually signed to support agriculture sector in the state. “This MoU has been actualised with the research and training institute set up to advance research in agriculture, encourage participation in farming and as well improve on the agricultural productivity in the state. This initiative aimed at improving on the agricultural agenda of the state, getting youths attracted to farming, exposing farmers to modern and mechanised farming techniques and as well increase agricultural productivity”, he added. On why the state decided to partner IITA, Aregbesola said the decision was taken having realised the agricultural poor yielding culture in the state, explaining that “Osun is the highest producer of cassava in Nigeria but even at that, the state produces just 16 metric tons per hectare which is far from expectation. He added, “We partner this international institute to deepen our commitment to massive food production in the state and ensure that the farmers’ yields are improved geometrically. “For instance, Osun is known to be the highest producer of cassava, but with this feat, our production is poor while the yield per hectare is between 15/16 metric ton per hectare. This is widely far from reality while compare with what those who have advanced on the production of cassava have per hectare, and it is for this reason that reached a compromise with IITA to support our farmers for greater productivity. “As I am speaking now, what we produce as far as cassava production is concerned has increased tremendously as it has increased from 16 metric tons per hectare to 40 metric tons per hectare. It is our belief that with this partnership, Osun farmers most especially the existing ones would begin to experience a new life in the agriculture sector while youth would also be encouraged to farming”, Aregbesola remarked. Earlier, the Deputy Director General, International Institute of Tropical Agriculture (IITA), Professor Michael Abberton, said IITA partnered Osun government having realised the keen interest of the state to revamp agriculture sector. He described the state’s commitment to agriculture revolution as remarkable; a step he said would be advanced by the IITA to ensure the actualisation of the state dreams in the agriculture sector.